STUDI PIROLISIS MIKROALGA Spirulina platensis TERHADAP KONSENTRASI PRODUK TURUNAN PROTEIN - Wahyuni, Ade Putri; Subagyono, RR Dirgarini Julia Nurlianti; Gunawan, Rahmat (Jurusan Kimia Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas Mulawarman, 2024)
Pyrolysis study of microalgae Spirulina platensis using Pyrolysis-Gas Chromatography-Mass Spectrometry (Py-GC/MS) instrument has been conducted. Based on the percent area value of pyrolysis products identified on the pyrogram, the concentration of Spirulina platensis pyrolysis products resulting from thermal decomposition of protein was 6.27%. Keywords: Pyrolysis, Spirulina platensis, Py-GC/MS.